Scientific approaches of professor I. I. Gorelik to the philosophy of penalty, imprisonment and the principles of punishability - Shidlovsky, Andrei V. (Journal of the Belarusian State University. Law, 2021)
The author studies the scientific and philosophical views of professor I. I. Gorelik in the aspects of the concept of punishment and the essence of the phenomenon of freedom of will, the principles of sentencing and differentiation of sanctions, and the application of deprivation of liberty. The author considers the grounds for differentiation of criminal punishability for crimes dangerous to life and health in the current Criminal Code of the Republic of Belarus from the perspective of I. I. Gorelik teaching on their specific gradation. The author analyses the legislative assessment of the severity of crimes that are dangerous to life and health, within the selected forms: leaving in danger and putting in danger. The author substantiates the proposals for eliminating the disproportions in the punishability of the group of sanctions of the considered criminal law norms.